Implementasi Kurikulum Syariah pada Siswa Kelas 2 SD Muhammadiyah Program Khusus Kottabarat Surakarta - Saputri, Neki; , Dra. Ratnasari Diah Utami, M. Si (2017)
This study aims to describe: 1) the implemetation of sharia based education curriculum in grade 2 students of SD Muhammadiyah Surakarta Kottabarat Special Program, 2) barriers that occur in the applications of sharia curriculum, and 3) solution of the obstacles that occur in the application of sharia curriculum. The research is a qualitative reseacrh with descriptive research design. Informants in this study is the head of the school, 2 grade teachers, parents and students in grade 2. The data collection tehniques used were interviews, observation and documenttion. The data have been obtained in the test were analyzed by four stages of data collection, data reduction, data presentation and conclusion. The result of this study indicate the sharia curriculum implementation such as: 1) the concept of sharia curriculum includes, integrated into general learning (National) to the Islamic based learning, which is based on the Qur'an and Hadith, 2) learning activities begins with reading the Quran/Iqro, 3) method used is a method in the curriculum2013, 4) students activity includes activities in the classroom and outside the calassroom, 5)curriculum implementation of sharia every material integrated into the religisu values of Islam rooted which is in accordance with the material, 6) an increase in occur in spritual to students both within the school and home environment, barries that occur in the application of sharia curriculum like, 1) teachers who lack adequate understanding, 2) teachers have difficulty in reading passagers convey the Qur'an, to students in grade 2, 3) the commotion between the students with each other. The solution in overcoming the barriers that occur such as: 1) held a training workshop and an evalution once a week, 2) teachers rewrite Arabic writing on the chalkboard, and what they mean, 3) giving pinishment and changing teachers teaching methods.